Analysis of Damage to Reinforced Concrete Beams Under Explosive Effects of Different Shapes, Equivalents, and Distances - Yu Ma; Rongyue Zheng; Wei Wang; Chenzhen Ye; Wenzhe Luo; Sihao Shen (Buildings)
Optimizing structural resistance against blast loads critically depends on the effects of different explosive shapes, equivalents, and distances on the damage characteristics of reinforced concrete beams. This study bridges the knowledge gap in understanding how these factors influence damage mechanisms through close-range air blast experiments and LS-DYNA numerical simulations. Key damage characteristics, such as craters, overpressure, impulse, time-history displacement, and residual mid-span displacement of reinforced concrete beams, were thoroughly analyzed. Results show that cuboid-shaped explosives cause the greatest damage, with the most severe effects observed at shorter distances and higher charge weights, including an increase in mid-span displacement of up to 16.3 cm. The study highlights the pivotal role of explosive geometry, charge weight, and standoff distance in shock wave propagation and structural failure and proposes an optimized damage criterion to enhance predictive capabilities for reinforced concrete beams under blast loads.